Parent involvement and achievement of full inclusion special needs students in design and technology - Abd Rani, Norhaslinda; Mat Rashid, Abdullah (Technoarete Research And Development Association, 2022)
Abstract: The implementation of inclusion in Malaysia demands the involvement of parents in the education of special needs students because empirical studies have proven that the involvement of parents can improve their academic achievement. This study aims to find out parent involvement and achievement of full inclusion special needs students in Design and Technology. Questionnaires were administered to 171 respondents in Klang Valley. This study has found that the involvement of parents in their children's learning and achievement of full inclusion special needs students in Design and Technology were low. The relationship between parent involvement and achievement of full inclusion special needs students in Design and Technology were tested using correlational method. A positive correlation was found between parent involvement and achievement of full inclusion special needs students in Design and Technology. This study recommends that parents be actively and effectively involved with their children’s learning either at home or at school so then the quality of inclusion and achievement of their children can be improved.